2019
DOI: 10.17509/jare.v1i1.15728
|View full text |Cite
|
Sign up to set email alerts
|

The Existence of Pedestrian in Jakarta

Abstract: Pedestrian is part of urban elements that have a significant role in forming a city. In the pedestrian, social interactions will be created which further strengthen relations between elements in the city. Cities in Europe are the best examples of city pedestrian planning. There walking is more comfortable and enjoyable, with the city being created by the streetscape and the humanist city order. Whereas in cities in developing countries like Jakarta, the city planning has not accommodated pedestrians at all.   … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Some of these variables were also mentioned in Aghaabbasi, M et al [20], which was conducted on the pedestrian path in Johor Bahru District, Malaysia, with some of those needed to be improved including seating area, effective sidewalk width, and lighting. Moreover, another study on the city of Thiruvananthapuram, India, showed the need to improve street light as part of the requirements to increase pedestrian satisfaction [23], whereas shades are reported to be important to protect pedestrians in tropical countries from hot weather [24].…”
Section: Performance Of the Pedestrian Lanementioning
confidence: 99%
See 2 more Smart Citations
“…Some of these variables were also mentioned in Aghaabbasi, M et al [20], which was conducted on the pedestrian path in Johor Bahru District, Malaysia, with some of those needed to be improved including seating area, effective sidewalk width, and lighting. Moreover, another study on the city of Thiruvananthapuram, India, showed the need to improve street light as part of the requirements to increase pedestrian satisfaction [23], whereas shades are reported to be important to protect pedestrians in tropical countries from hot weather [24].…”
Section: Performance Of the Pedestrian Lanementioning
confidence: 99%
“…The plan of these cities does not accommodate pedestrians, with the sidewalk designed in Jakarta observed not to be humanist, thereby forcing commuters to ride cars. The paths are designed to be next to the road and have insufficient width to accommodate pedestrians' volume, thereby creating an unsafe and very uncomfortable condition for the pedestrians [24].…”
Section: D a Bmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, according to Carr (1992), public space is a shared space where the public can carry out various activities and are free of charge to enter the area (Susanti et al, 2020) (Mardiana et al, 2019). Activities that occur can be in the form of daily routines, activities in a certain season or an event (Permana et al, 2019) (Saha et al, 2020).…”
Section: Introductionmentioning
confidence: 99%